Awareness and knowledge of heterozygous familial hypercholesterolemia among Serbian pediatricians - Bjelakovic, Ljiljana; Stosic, Lazar; Klisic, Aleksandra; Jovic, Marko; Stankovic, Sanja; Stankovic, Aleksandra; Pantelic, Sasa; Zivkovic, Danijela; Vukovic, Vladimir; Bjelakovic, Bojko (Frontiers in Pediatrics, 2023)
Objective Published reports describing awareness and knowledge of familial hypercholesterolemia (FH) among pediatricians are few and differ considerably across countries. We aimed to assess awareness and knowledge of the FH among pediatricians in Serbia. Methods A web-based cross-sectional study using a self-designed questionnaire was conducted during the annual congress of the Serbian Association of Preventive Pediatrics in 2020. Results A total of 141 pediatricians completed the questionnaire (response rate 16.1%). Overall, 91% of participants have knowledge about genetic inheritance of FH, 84.3% were aware of long-term health risks of FH, 77% were familiar with normal cholesterol values in children and 71% knew the FH prevalence in the general population. On the other hand, only 36.8% declared that they were familiar with international guidelines for FH drug treatment and only 26.2% declared to have patients with FH. Conclusion There is a substantial lack of practical clinical knowledge among Serbian pediatricians on managing children with FH. In addition, an extremely low questionnaire response rate (16.1%) suggests that most pediatricians are not aware of the clinical importance of FH in childhood.